Efektivitas Kebijakan Free Trade Zone Bintan Terhadap Investasi di Kawasan Bintan - syaputra dicky; Dhani Akbar; Ryan Anggria Pratama (Social Issues Quarterly, 2023)
Based on Government regulation Number 41 of 2017 concerning the Bintan free trade zone and port, Article 1 Paragraph (2) stipulates that Bintan free trade zone area is enclave, an enclave area means that the Bintan free trade zone is only a pieces of it, not the entire Bintan area. It is feared to affect investors who invest which in 2022 for the invesment realization target is still not fullfilled. This study aims to determine the effectiveness of the policy setting which in this study uses qualitative research method with a descriptive method approach. Based on policy indicators, the establishment of bintan enclave free trade zone is still not effective, seeing the development and trends in the Bintan region with a free trade zone area that is only like that, it is not enough because there are many areas that should be developed. This also policy provides problems in terms of monitoring goods that are not supposed to leave the free trade zone area due to its enclave nature. For proper implementation, the bintan concession agency in managing the area conducts promotions and infrastructure development in order to attract investors so that they can provide the right services for them. And for the right target, the investment realization target set in 2022 cannot be met due to several factors such as investment plans that cannot be implemented and also the investment realization target set too high without seeing realistic conditions.